Utility of magnetic resonance imaging in the diagnosis of unsuspected cases of Parsonage-Turner syndrome: two case reports - Kumar, Ishan (BioMed Central, 2013)
INTRODUCTION: MRI is becoming increasingly important in the evaluation of shoulder pain, especially in the diagnosis of rotator cuff injuries and conditions that mimic them. Parsonage-Turner syndrome is a well-defined clinical entity that presents with acute-onset shoulder pain and weakness, often first recognized on magnetic resonance imaging scans. CASE PRESENTATION: We studied magnetic resonance imaging features of two Asian men (ages 24 and 31 years) who presented with variable-onset shoulder pain and weakness. Magnetic resonance imaging revealed increased T2-weighted signal intensity of supraspinatus and infraspinatus muscles in both patients. CONCLUSION: Magnetic resonance imaging findings are distinctive, although nonspecific, in cases of Parsonage-Turner syndrome, and knowledge of the imaging and clinical features of this disease enable clinicians to arrive at the correct diagnosis and guide appropriate management.